PENGARUH LITERASI KEUANGAN SYARI’AH DAN PEMBAYARAN DIGITAL (E-WALLET) TERHADAP PENINGKATAN OMZET USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) PADA KELURAHAN GEDUNG JOHOR - Riki Gunawan; Arifa Pratami; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Thi s stud y ai ms to analyze the i nflue nce of I slami c fi nanci al li te racy and d i gi tal payme nt (e -walle t) on i ncre asi ng the turnove r of Mi cro, Small, and Me d i um E nte rpri se s (MSME s) i n Ge d ung Johor Vi llage . Thi s re se arch i s moti vate d by the i mportance of shari a-base d fi nanci al manage me nt and the uti li zati on of d i gi tal payme nt te chnology to support busi ne ss d e ve lopme nt i n the d i gi tal e ra. Thi s stud y e mploye d a quanti tati ve approach wi th an associ ati ve re se arch d e si gn. The populati on i n thi s stud y consi ste d of 110 MSME actors, wi th a sample of 86 re spond e nts d e te rmi ne d usi ng the Slovi n formula and purposi ve sampli ng te chni que . D ata we re colle cte d through que sti onnai re s usi ng a Li ke rt scale and analyze d usi ng vali d i ty te sts, re li abi li ty te sts, classi cal assumpti on te sts, multi ple li ne ar re gre ssi on analysi s, t-te st, F-te st, and coe ffi ci e nt of d e te rmi nati on. The re sults showe d that parti ally, I slami c fi nanci al li te racy had a posi ti ve and si gni fi cant e ffe ct on i ncre asi ng MSME turnove r, wi th a t-count of 5.912 > t-table of 1.989 and a si gni fi cance value of 0.000 < 0.05, whi le d i gi tal payme nt (e -walle t) also had a posi ti ve and si gni fi cant e ffe ct on i ncre asi ng MSME turnove r, wi th a t-count of 4.668 > t-table of 1.989 and a si gni fi cance value of 0.000 < 0.05. Si multane ously, I slami c fi nanci al li te racy and d i gi tal payme nt (e -walle t) had a posi ti ve and si gni fi cant e ffe ct on i ncre asi ng MSME turnove r, wi th an F-count of 31.816 > F-table of 3.105 and a si gni fi cance value of 0.000 < 0.05. The coe ffi ci e nt of d e te rmi nati on (R²) of 0.434 i nd i cate s that 43.4% of the vari ati on i n MSME turnove r i ncre ase can be e xplai ne d by the se two vari able s, whi le the re mai ni ng 56.6% i s i nflue nce d by othe r factors outsi d e thi s stud y. Thus, i mprovi ng I slami c fi nanci al li te racy and opti mi zi ng the use of e -walle ts can be i mportant factors i n e ncouragi ng the i ncre ase of MSME turnove r i n Ge d ung Johor Vi llage .